The burden of chronic respiratory disease in the Western Cape - Carkeek, Emma Claire (Department of Public Health and Family Medicine, 2019)
Chronic respiratory disease (CRD), comprised mainly of asthma and chronic obstructive lung disease (COPD), is responsible for significant morbidity and mortality worldwide. Although asthma and COPD cannot be cured, they can be controlled using appropriate medications. Poorly controlled CRD is associated with significantly poorer quality of life and mortality for patients, an increased burden on the healthcare system, and a negative economic impact due to loss of productivity. CRD is underdiagnosed, undertreated and poorly controlled, especially in low- and middle-income countries. Improving control of CRD would result in improved quality of life for patients and a reduced burden on the healthcare system and economy. Despite the increase in burden of CRD globally, limited data are available on the burden of CRD in South Africa. Such data are essential if appropriate measures are to be put in place to address these needs. In this mini-dissertation, I aimed to describe the symptomatic burden of disease and levels of treatment in adults with CRD attending primary healthcare facilities in the Western Cape. Additionally, I aimed to identify predictors of both the quality of life and receipt of treatment in this population. This study was a secondary analysis of the baseline data collected during the Primary Care 101 (PC101) trial, a large pragmatic cluster randomised controlled trial conducted in 38 primary healthcare clinics in the Eden and Overberg districts of the Western Cape between 2011 and 2012. The study population for the current study was limited to the 1 157 participants enrolled in the CRD cohort of the PC101 trial. Part A of this mini-dissertation comprises the research protocol which was submitted to, and approved by, the University of Cape Town Faculty of Health Sciences Human Research Ethics Committee. Part B comprises the literature review, which outlines the prevalence and increasing burden of CRD both globally and in South Africa. As demonstrated in many studies from a wide variety of countries, the literature supports that CRD is underdiagnosed, undertreated, and has a significant impact both on affected individuals as well as healthcare systems and economies. Part C includes the journal-ready manuscript. Findings confirm a high burden of symptoms and activity limitation, indicating a poor quality of life amongst this population. Findings also suggest undertreatment, with 40% of patients not receiving treatment for CRD despite being symptomatic. More respiratory symptoms were associated with male sex, a positive screen for depression, previous tuberculosis, previous smoking, more activity limitation and current receipt of treatment for CRD. Greater activity limitation was associated with unemployment, diabetes, a positive screen for depression, more respiratory symptoms, recent hospital admission and receiving treatment for CRD. Participants were more likely to be on treatment if they were older, more symptomatic or had greater activity limitation due to their respiratory condition. Treatment was less likely in participants who screened positive for depression, were current smokers, had increased recent clinic visits or a recent hospital admission. In summary, we found a high burden of symptoms and activity limitation, and of undertreatment, possibly contributed to by under-recognition of respiratory disease among patients attending primary care clinics in the Western Cape. Depression, a history of previous tuberculosis and unemployment are common features in such patients. Potential interventions are to introduce a systematic approach to CRD diagnosis in primary care clinics that includes screening for depression, improving availability of essential drugs for the management of CRD, and preventive strategies such as more effective tuberculosis control, and support and pharmacotherapy to assist smokers to quit.